Nest Success of Semi-Natural Hatching Program for Moluccan Scrubfowl (Eulipoa wallacei) in Mamuya Village, North Halmahera Regency - Boleu, Fiktor Imanuel; Simanjuntak, Radios; Tuny, Margaretha Tabita; Kailola, Jacob; Lewerissa, Ebedly; Ganna, Melisa Angela; Sudrajat, Tania Ayu; Maatoke, Cornelia Dolfina; Manik, Eppi (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2024)
Protecting the nesting habitat of the Moluccan Scrubfowl (Eulipoa wallacei) is important to conserve the population of this endemic species in North Maluku. The success rate of semi-natural hatching nests of Moluccan Scrubfowl varies in each hatchery conservation location. This study aims to determine the nest success of semi-natural hatching program of Moluccan Scrubfowl in Mamuya Village, North Halmahera Regency. A field experiment approach was used to estimate nest success in semi-natural (in-situ) incubation treatments. Eggs used for the semi-natural hatching treatment were collected from landowner egg collecting activities at four Moluccan Scrubfowl nesting sites. In semi-natural hatching, each bird egg was placed in 60 cm of sand with a minimum distance of 10 cm between eggs (egg density adjusted to the number of eggs planted). A total of 116 Moluccan Scrubfowl eggs were planted over four planting periods and during the natural incubation period the eggs hatched producing 96 chicks. The nest success of the semi-natural hatching program for Moluccan Scrubfowl in Mamuya Village has a high success value of 0,835 (83,52%). This optimal success indicates that incubation in the chick embryo formation process is stable on the sand substrate. The mean incubation time interval for hatching eggs lasted 74 days (interval 72 - 76 days)